Um olhar para a questão do aparente desinteresse pelo ensino-aprendizagem de língua inglesa por alunos da escola pública - Almeida, Francisco Fernando Lima (2012)
This study aims at understanding reasons for the apparent lack of interest in learning English by students in a public school in the greater São Paulo area. Theoretical support for the study are Moita Lopes (2006), Stake (1998), Nunan (1992), Travaglia (2002) Celani (2002), Vygotsky (1934/1998; 1930/1993) among others. Data were collected by means of a questionnaire and semi-structured interviews involving 31 students, 16 in the 5th grade and 15 in the 6th grade. Results show that the apparent lack of interest is the result of social factors. They also show that nearly all students would be interested in learning English at school